THE IMPACT OF ELECTRONIC HUMAN RESOURCE MANAGEMENT STRATEGIES ON ORGANIZATIONAL FLEXIBILITY - Hasan Fadhil Al Husseini; Amer Abed Kareem Al-Thabhawee (ZILLZELL MEDIA PRIMA, 2024)
Through a theoretical framework, this study aimed to identify definitions of Organizational Flexibility by covering the definitions proposed by many researchers and trying to reach a new definition. Previous studies have identified many benefits that can be achieved using organizational resilience in organizations. In addition, this study summarized these benefits and identified the most frequently mentioned benefits through a review of previous studies. The study measured the impact of Electronic Human Resource Management Strategies on (OF) in Iraqi pharmaceutical companies through a service of 180 employees in 20 Iraqi companies producing human drugs Partial Covariance-Based Structural Equation Modeling (CB-SEM) were used in the statistical program (Smart PLS (version 4.0.8.9) as a statistical method for data analysis. The results of the study showed a significant effect of E-HRMS on (OF)in Iraqi pharmaceutical companies and the highest level of (OF) in Iraqi pharmaceutical companies. The most important recommendation for this study was that if organizations want to encourage the adoption of new work methods such as (OF), there must be a link between employee’s incentives and employee learning for this new technological skill.